An Analysis of Reading Texts - Desi Andriani (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2019)
The purposes of this research is to know the readability, exploitability and suitability of content of reading materials.  This research is a descriptive research. The sources of the data of this research are reading materials of recount, narrative dan procedure texts. The texts are from Look Ahead and internet. The texts are used by English teachers at first grade at first semester. The instrument that is used analysis format. Data analyzed based on indicator readability, exploitability and suitability of content.